Effects of Low-Level Artificial Light at Night on Kentucky Bluegrass and an Introduced Herbivore - Crump, Morgan C.; Brown, Cassandra; Griffin-Nolan, Robert J.; Angeloni, Lisa; Lemoine, Nathan P.; Seymoure, Brett M. (Frontiers in Ecology and Evolution, 2021)
Increasing evidence suggests that artificial light at night (ALAN) can negatively impact organisms. However, most studies examine the impacts of ALAN on a single species or under high levels of artificial light that are infrequent or unrealistic in urban environments. We currently have little information on how low levels of artificial light emanating from urban skyglow affect plants and their interactions with herbivores. We examined how low levels of ALAN affect grass and insects, including growth rate, photosynthesis, and stomatal conductance in grass, and foraging behavior and survival in crickets. We compared growth and leaf-level gas exchange of Kentucky Bluegrass (Poa pratensis) under low-levels of ALAN (0.3 lux) and starlight conditions (night light at 0.001 lux). Furthermore, each light treatment was divided into treatments with and without house crickets (Acheta domesticus). Without crickets present, bluegrass grown under artificial light at night for three weeks grew taller than plants grown under natural night light levels. Once crickets were introduced at the end of week three, grass height decreased resulting in no measurable effects of light treatment. There were no measurable differences in grass physiology among treatments. Our results indicate that low levels of light resulting from skyglow affect plant growth initially. However, with herbivory, ALAN effects on grass may be inconsequential. Gaining an understanding of how ALAN effects plant-insect interactions is critical to predicting ecological and evolutionary consequences of anthropogenic disturbance.